Toward a Transformational Africa-U.S. STEM University Initiative: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
STEM (science, technology, engineering, and mathematics) plays a key role in accelerating economic growth and developing innovative solutions to pressing challenges facing the African continent. Over the past few decades, much work has been done to develop university systems in African countries in recognition of the role that high-caliber teaching and research in STEM fields play in economic development. African universities and their governments have made many of these gains through partnering across countries and sectors. Often, however, these efforts are based on individual connections and do not lead to long-term change. Inspired by STEM's potential to tackle African and global challenges, a group of academic leaders has come together to explore a synergistic approach to transform African institutions of higher education and increase the global engagement of U.S. institutions. They developed an initial vision for a next-generation Africa-U.S. STEM initiative that would take place for at least 10 years, with funds of at least $10 million annually from governments, the private sector, philanthropies, and other organizations. To obtain input from stakeholders on how such an initiative could develop, the group held a virtual workshop March 14-16, 2022, convened by the National Academies of Sciences, Engineering, and Medicine. This publication summarizes the presentations and discussions of the workshop.
Keywords: Education

The Continuing Epidemiological Transition in Sub-Saharan Africa: A Workshop Summary - National Research Council (The National Academies Press, 2012)
Among the poorest and least developed regions in the world, sub-Saharan Africa has long faced a heavy burden of disease, with malaria, tuberculosis, and, more recently, HIV being among the most prominent contributors to that burden. Yet in most parts of Africa-and especially in those areas with the greatest health care needs-the data available to health planners to better understand and address these problems are extremely limited. The vast majority of Africans are born and will die without being recorded in any document or spearing in official statistics. With few exceptions, African countries have no civil registration systems in place and hence are unable to continuously generate vital statistics or to provide systematic information on patterns of cause of death, relying instead on periodic household-level surveys or intense and continuous monitoring of small demographic surveillance sites to provide a partial epidemiological and demographic profile of the population. In 1991 the Committee on Population of the National Academy of Sciences organized a workshop on the epidemiological transition in developing countries. The workshop brought together medical experts, epidemiologists, demographers, and other social scientists involved in research on the epidemiological transition in developing countries to discuss the nature of the ongoing transition, identify the most important contributors to the overall burden of disease, and discuss how such information could be used to assist policy makers in those countries to establish priorities with respect to the prevention and management of the main causes of ill health. This report summarizes the presentations and discussions from a workshop convened in October 2011 that featured invited speakers on the topic of epidemiological transition in sub-Saharan Africa. The workshop was organized by a National Research Council panel of experts in various aspects of the study of epidemiological transition and of sub-Saharan data sources. The Continuing Epidemiological Transition in Sub-Saharan Africa serves as a factual summary of what occurred at the workshop in October 2011.
Keywords: Behavioral and Social Sciences; Health and Medicine

Preparing for the Future of HIV/AIDS in Africa: A Shared Responsibility - Institute of Medicine (The National Academies Press, 2011)
HIV/AIDS is a catastrophe globally but nowhere more so than in sub-Saharan Africa, which in 2008 accounted for 67 percent of cases worldwide and 91 percent of new infections. The Institute of Medicine recommends that the United States and African nations move toward a strategy of shared responsibility such that these nations are empowered to take ownership of their HIV/AIDS problem and work to solve it.
Keywords: Health and Medicine

Sharing Research Data to Improve Public Health in Africa: A Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
Sharing research data on public health issues can promote expanded scientific inquiry and has the potential to advance improvements in public health. Although sharing data is the norm in some research fields, sharing of data in public health is not as firmly established. In March 2015, the National Research Council organized an international conference in Stellenbosch, South Africa, to explore the benefits of and barriers to sharing research data within the African context. The workshop brought together public health researchers and epidemiologists primarily from the African continent, along with selected international experts, to talk about the benefits and challenges of sharing data to improve public health, and to discuss potential actions to guide future work related to public health research data sharing. Sharing Research Data to Improve Public Health in Africa summarizes the presentations and discussions from this workshop.
Keywords: Policy for Science and Technology; Health and Medicine

Recent Fertility Trends in Sub-Saharan Africa: Workshop Summary - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Fertility rates and population growth influence economic development. The marked declines in fertility seen in some developing nations have been accompanied by slowing population growth, which in turn provided a window of opportunity for rapid economic growth. For many sub-Saharan African nations, this window has not yet opened because fertility rates have not declined as rapidly there as elsewhere. Fertility rates in many sub-Saharan African countries are high: the total rate for the region is estimated to be 5.1 births per woman, and rates that had begun to decline in many countries in the region have stalled. High rates of fertility in these countries are likely to contribute to continued rapid population growth: the United Nations projects that the region's population will increase by 1.2 billion by 2050, the highest growth among the regions for which there are projections. In June 2015, the Committee on Population organized a workshop to explore fertility trends and the factors that have influenced them. The workshop committee was asked to explore history and trends related to fertility, proximate determinants and other influences, the status and impact of family planning programs, and prospects for further reducing fertility rates. This study will help donors, researchers, and policy makers better understand the factors that may explain the slow pace of fertility decline in this region, and develop methods to improve family planning in sub-Saharan Africa.
Keywords: Behavioral and Social Sciences

The Ebola Epidemic in West Africa: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The most recent Ebola epidemic that began in late 2013 alerted the entire world to the gaps in infectious disease emergency preparedness and response. The regional outbreak that progressed to a significant public health emergency of international concern (PHEIC) in a matter of months killed 11,310 and infected more than 28,616. While this outbreak bears some unique distinctions to past outbreaks, many characteristics remain the same and contributed to tragic loss of human life and unnecessary expenditure of capital: insufficient knowledge of the disease, its reservoirs, and its transmission; delayed prevention efforts and treatment; poor control of the disease in hospital settings; and inadequate community and international responses. Recognizing the opportunity to learn from the countless lessons of this epidemic, the National Academies of Sciences, Engineering, and Medicine convened a workshop in March 2015 to discuss the challenges to successful outbreak responses at the scientific, clinical, and global health levels. Workshop participants explored the epidemic from multiple perspectives, identified important questions about Ebola that remained unanswered, and sought to apply this understanding to the broad challenges posed by Ebola and other emerging pathogens, to prevent the international community from being taken by surprise once again in the face of these threats. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

The Emerging Threat of Drug-Resistant Tuberculosis in Southern Africa: Global and Local Challenges and Solutions: Summary of a Joint Workshop by the Institute of Medicine and the Academy of Science of South Africa - Institute of Medicine (The National Academies Press, 2011)
Tuberculosis (TB) kills approximately 4,500 people worldwide every day. While most cases of TB can be treated with antibiotics, some strains have developed drug resistance that makes their treatment more expensive, more toxic and less effective for the patient. The IOM Forum on Drug Discovery, Development, and Translation and the Academy of Science of South Africa held a workshop to discuss ways to fight the growing threat of drug-resistant TB.
Keywords: Health and Medicine

Aging in Sub-Saharan Africa: Recommendations for Furthering Research - National Research Council (The National Academies Press, 2006)
In sub-Saharan Africa, older people make up a relatively small fraction of the total population and are supported primarily by family and other kinship networks. They have traditionally been viewed as repositories of information and wisdom, and are critical pillars of the community but as the HIV/AIDS pandemic destroys family systems, the elderly increasingly have to deal with the loss of their own support while absorbing the additional responsibilities of caring for their orphaned grandchildren. Aging in Sub-Saharan Africa explores ways to promote U.S. research interests and to augment the sub-Saharan governments' capacity to address the many challenges posed by population aging. Five major themes are explored in the book such as the need for a basic definition of "older person," the need for national governments to invest more in basic research and the coordination of data collection across countries, and the need for improved dialogue between local researchers and policy makers. This book makes three major recommendations: 1) the development of a research agenda 2) enhancing research opportunity and implementation and 3) the translation of research findings.
Keywords: Behavioral and Social Sciences

Lost Crops of Africa: Volume II: Vegetables - National Research Council (The National Academies Press, 2006)
This report is the second in a series of three evaluating underexploited African plant resources that could help broaden and secure Africa's food supply. The volume describes the characteristics of 18 little-known indigenous African vegetables (including tubers and legumes) that have potential as food- and cash-crops but are typically overlooked by scientists and policymakers and in the world at large. The book assesses the potential of each vegetable to help overcome malnutrition, boost food security, foster rural development, and create sustainable landcare in Africa. Each species is described in a separate chapter, based on information gathered from and verified by a pool of experts throughout the world. Volume I describes African grains and Volume III African fruits.
Keywords: Agriculture; Biology and Life Sciences

Down to Earth: Geographic Information for Sustainable Development in Africa - National Research Council (The National Academies Press, 2002)
In 1992, world leaders adopted Agenda 21, the work program of the 1992 U.N. Conference on Environment and Development. This landmark event provided a political foundation and action items to facilitate the global transition toward sustainable development. The international community marked the tenth anniversary of this conference in Johannesburg, South Africa, in August 2002. Down to Earth, a component of the U.S. State Department's "Geographic Information for Sustainable Development" project for the World Summit, focuses on sub-Saharan Africa with examples drawn from case-study regions where the U.S. Agency for International Development and other agencies have broad experience. Although African countries are the geographic focus of the study, the report has broader applicability. Down to Earth summarizes the importance and applicability of geographic data for sustainable development and draws on experiences in African countries to examine how future sources and applications of geographic data could provide reliable support to decision-makers as they work towards sustainable development. The committee emphasizes the potential of new technologies, such as satellite remote-sensing systems and geographic information systems, that have revolutionized data collection and analysis over the last decade.
Keywords: Earth Sciences; Environment and Environmental Studies

Lost Crops of Africa: Volume III: Fruits - National Research Council (The National Academies Press, 2008)
This book is the third in a series evaluating underexploited African plant resources that could help broaden and secure Africa's food supply. The volume describes 24 little-known indigenous African cultivated and wild fruits that have potential as food- and cash-crops but are typically overlooked by scientists, policymakers, and the world at large. The book assesses the potential of each fruit to help overcome malnutrition, boost food security, foster rural development, and create sustainable landcare in Africa. Each fruit is also described in a separate chapter, based on information provided and assessed by experts throughout the world. Volume I describes African grains and Volume II African vegetables.
Keywords: Agriculture; Biology and Life Sciences

Strengthening Human Resources Through Development of Candidate Core Competencies for Mental, Neurological, and Substance Use Disorders in Sub-Saharan Africa: Workshop Summary - Institute of Medicine (The National Academies Press, 2013)
One of the largest treatment gaps for mental, neurological, and substance use (MNS) disorders in the world can be seen in Sub-Saharan Africa (SSA). According to the World Health Organization (WHO), about 80% of people with serious MNS disorders living in low- and middle-income countries do not receive needed health services. A critical barrier to bridge this treatment gap is the ability to provide adequate human resources for the delivery of essential interventions for MNS disorders. An international workshop was convened in 2009, by the .S. Institute of Medicine (IOM) Forum on Neuroscience and Nervous Systems Disorders and the Uganda National Academy of Sciences (UNAS) Forum on Health and Nutrition, to bring together stakeholders from across SSA and to foster discussions about improving care for people suffering from MNS disorders and what steps, with potential for the greatest impact, might be considered to bridge the treatment gap. Due to the broad interest to further examine the treatment gap, the IOM forum organized a second workshop in Kampala, Uganda on September 4 and 5, 2012. The workshop's purpose was to discuss candidate core competencies that providers might need to help ensure the effective delivery of services for MNS disorders. The workshop focused specifically on depression, psychosis, epilepsy, and alcohol use disorders. Strengthening Human Resources Through Development of Candidate Core Competencies for Mental, Neurological, and Substance Use Disorders in Sub-Saharan Africa: Workshop Summary outlines the presentations and discussions by expert panelists and participants of the plenary sessions of the workshop. This summary includes an overview of challenges faced by MNS providers in the SSA, perspectives on the next steps, the 2009 workshop, and more.
Keywords: Health and Medicine

Improving Access to Essential Medicines for Mental, Neurological, and Substance Use Disorders in Sub-Saharan Africa: Workshop Summary - Institute of Medicine (The National Academies Press, 2014)
In 2011 the Grand Challenges in Global Mental Health initiative identified priorities that have the potential to make a significant impact on the lives of people with mental, neurological, and substance use disorders. Reduction of the cost and improvement of the supply of effective medicines was highlighted as one of the top five challenges. For low- and middle-income countries, improving access to appropriate essential medicines can be a tremendous challenge and a critical barrier to scaling up quality care for mental, neurological, and substance use disorders. Reduction of cost and improvement of the supply of effective medicines has the potential to significantly impact the lives of patients with these disorders. Improving Access to Essential Medicines for Mental, Neurological, and Substance Use Disorders in Sub-Saharan Africa is the summary of a workshop convened by the Institute of Medicine Neuroscience Forum in January 2014 in Addis Ababa, Ethiopia to discuss opportunities for achieving long-term affordable access to medicines for these disorders. This report examines challenges and opportunities for improving access to essential medicines in four critical areas: demand, selection, supply chains, and financing and pricing. The report also discusses successful activities that increase access to essential medicines both within Sub-Saharan Africa and in other developing countries, and considers the role of governments, nongovernmental organizations, and private groups in procurement of essential medicines for mental, neurological, and substance use disorders.
Keywords: Health and Medicine

Emerging Technologies to Benefit Farmers in Sub-Saharan Africa and South Asia - National Research Council (The National Academies Press, 2009)
Increased agricultural productivity is a major stepping stone on the path out of poverty in sub-Saharan Africa and South Asia, but farmers there face tremendous challenges improving production. Poor soil, inefficient water use, and a lack of access to plant breeding resources, nutritious animal feed, high quality seed, and fuel and electricity-combined with some of the most extreme environmental conditions on Earth-have made yields in crop and animal production far lower in these regions than world averages. Emerging Technologies to Benefit Farmers in Sub-Saharan Africa and South Asia identifies sixty emerging technologies with the potential to significantly improve agricultural productivity in sub-Saharan Africa and South Asia. Eighteen technologies are recommended for immediate development or further exploration. Scientists from all backgrounds have an opportunity to become involved in bringing these and other technologies to fruition. The opportunities suggested in this book offer new approaches that can synergize with each other and with many other activities to transform agriculture in sub-Saharan Africa and South Asia.
Keywords: Agriculture

Mental, Neurological, and Substance Use Disorders in Sub-Saharan Africa: Reducing the Treatment Gap, Improving Quality of Care: Summary of a Joint Workshop by the Institute of Medicine and the Uganda National Academy of Sciences - Institute of Medicine (The National Academies Press, 2010)
Millions of people in sub-Saharan Africa suffer from mental, neurological, and substance use (MNS) disorders, and most do not have the resources to obtain treatment. The Uganda National Academy of Sciences and the Institute of Medicine hosted a workshop to discuss the state of care for MNS disorders in sub-Saharan Africa.
Keywords: Health and Medicine

Stronger Food and Drug Regulatory Systems Abroad - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Ensuring the safety of food and the quality and safety of medicines in a country is an important role of government, made more complicated by global manufacturing and international trade. By recent estimates, unsafe food kills over 400,000 people a year, a third of them children under 5, mostly in low- and middle-income countries; every year poor quality medicines cause about 70,000 excess deaths from childhood pneumonia and roughly 8,500 to 20,000 malaria deaths in sub-Saharan Africa alone. The Federal Drug Administration (FDA) Office of Global Policy and Strategy is charged with improving capacity of the agency's foreign counterpart offices and increasing understanding of the importance of regulatory systems for public health, development, and trade. At the request of the FDA, this study sets out a strategy to support good quality, wholesome food and safe, effective medical products around the world. Its goal is to build on the momentum for strengthening regulatory systems and to set a course for sustainability and continued progress. The 2012 report Ensuring Safe Food and Medical Products Through Stronger Regulatory Systems Abroad outlined strategies to secure international supply chains, emphasized capacity building and support for surveillance in low- and middle-income countries, and explored ways to facilitate work sharing among food and medical product regulatory agencies. This new study assess progress made and the current regulatory landscape.
Keywords: Food and Nutrition; Health and Medicine

Providing Reliable and Affordable Electricity in Countries with Energy Deficits: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
The National Academies of Sciences, Engineering, and Medicine organized an international workshop on February 27 - March 1, 2018 to discuss increasing access to reliable and affordable electricity in energy deficit regions of the world. The workshop was meant to identify under-valued activities that are essential for major progress in expanding access to reliable and affordable electricity in energy-deficit regions, particularly in sub-Sahara Africa and southern Asia. This publication summarizes the presentations and discussions from the workshop.
Keywords: Energy and Energy Conservation

Public Transportation Systems as the Foundation for Economic Growth - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
TRB’s Transit Cooperative Research Program (TCRP) RRD 102: Public Transportation Systems as the Foundation for Economic Growth examines how transit investments are linked to economic growth and recovery in several cities in Turkey, Egypt, and South Africa.
Keywords: Transportation and Infrastructure

Preventing Intimate Partner Violence in Uganda, Kenya, and Tanzania: Summary of a Joint Workshop by the Institute of Medicine, the National Research Council, and the Uganda National Academy of Sciences - Institute of Medicine; National Research Council (The National Academies Press, 2015)
Globally, between 15-71 percent of women will experience physical and/or sexual abuse from an intimate partner at some point in their lifetime. Too often this preventable form of violence is repetitive in nature, occurring at multiple points across the lifespan. The prevalence of intimate partner violence is on the higher end of this spectrum in East Africa, with in-country demographic and health surveys indicating that approximately half of all women between the ages of 15-49 in Uganda, Kenya, and Tanzania having experienced physical or sexual abuse within a partnership. It is now widely accepted that preventing intimate partner violence is possible and can be achieved through a greater understanding of the problem; its risk and protective factors; and effective evidence-informed primary, secondary, and tertiary prevention. To that end, on August 11-12, 2014, the Institute of Medicine's Forum on Global Violence Prevention, in a collaborative partnership with the Uganda National Academy of Sciences, convened a workshop focused on informing and creating synergies within a diverse community of researchers, health workers, and decision makers committed to promoting intimate partner violence-prevention efforts that are innovative, evidence-based, and crosscutting. This workshop brought together a variety of stakeholders and community workers from Uganda, Kenya, and Tanzania to engage in a meaningful, multidirectional dialogue regarding intimate partner violence in the region. Preventing Intimate Partner Violence in Uganda, Kenya, and Tanzania summarizes the presentations and discussion of the workshop.
Keywords: Health and Medicine

Tendances Récentes de la Fécondité en Afrique Subsaharienne: Synthèse de l'Atelier - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
Note: This is the French translation of Recent Fertility Trends in Sub-Saharan Africa. Fertility rates and population growth influence economic development. The marked declines in fertility seen in some developing nations have been accompanied by slowing population growth, which in turn provided a window of opportunity for rapid economic growth. For many sub-Saharan African nations, this window has not yet opened because fertility rates have not declined as rapidly there as elsewhere. Fertility rates in many sub-Saharan African countries are high: the total rate for the region is estimated to be 5.1 births per woman, and rates that had begun to decline in many countries in the region have stalled. High rates of fertility in these countries are likely to contribute to continued rapid population growth: the United Nations projects that the region's population will increase by 1.2 billion by 2050, the highest growth among the regions for which there are projections. In June 2015, the Committee on Population organized a workshop to explore fertility trends and the factors that have influenced them. The workshop committee was asked to explore history and trends related to fertility, proximate determinants and other influences, the status and impact of family planning programs, and prospects for further reducing fertility rates. This study will help donors, researchers, and policy makers better understand the factors that may explain the slow pace of fertility decline in this region, and develop methods to improve family planning in sub-Saharan Africa.
Keywords: Behavioral and Social Sciences